Hubungan Usia Dan Paritas Ibu Dengan Kejadian Postpartum Blues Di PMB “W” Magetan - Oktavia Puspita Sari; Agung Suharto (Jurusan Kebidanan Politeknik Kesehatan Kemenkes Surabaya, 2021)
Indonesia's postpartum blues incidence is 50-70% of postpartum women, postpartum blues occur in postpartum women caused by several factors such as childbirth experience, increased hormones, infant behavior, maternal age, and parity. The aim of the study was to determine the relationship of age and parity with the incidence of postpartum blues in PMB